Evaluating the impact of different agropastoral practices on wind erosion in western Sahel - Paul-Alain Raynal; Jean-Louis Rajot; Beatrice Marticorena; Abdourahmane Tall; Baptiste Lemaire; Jean-Alain Civil; Diouma Cor Fall; Gualbert Seraphin Dorego; Ibrahima Sarr; Issa Faye; Ambre Emmendoerffer; Henri Guillaume; et al. (CATENA, 2025)

Pollution assessment around a big city in West Africa reveals high concentrations of microplastics and microbiologic contamination - Amidou Sonko; Patrice Brehmer; Guillaume Constantin de Magny; Gaël Le Pennec; Bissoume Sambe Ba; Ousmane Diankha; Mamadou Fall; Isabelle Linossier; Maryvonne Henry; Issa N’Diaye; Saliou Faye; Yoba Kande; et al. (Regional Studies in Marine Science, 2023)

Translational genomics for achieving higher genetic gains in groundnut - Manish K. Pandey; Arun K. Pandey; Rakesh Kumar; Chogozie Victor Nwosu; Baozhu Guo; Graeme C. Wright; Ramesh S. Bhat; Xiaoping Chen; Sandip K. Bera; Mei Yuan; Huifang Jiang; Issa Faye; et al. (Theoretical and Applied Genetics, 2020)
Key message Groundnut has entered now in post-genome era enriched with optimum genomic and genetic resources to facilitate faster trait dissection, gene discovery and accelerated genetic improvement for developing climate-smart varieties. Abstract Cultivated groundnut or peanut ( Arachis hypogaea ), an allopolyploid oilseed crop with a large and complex genome, is one of the most nutritious food. This crop is grown in more than 100 countries, and the low productivity has remained the biggest challenge in the semiarid tropics. Recently, the groundnut research community has witnessed fast progress and achieved several key milestones in genomics research including genome sequence assemblies of wild diploid progenitors, wild tetraploid and both the subspecies of cultivated tetraploids, resequencing of diverse germplasm lines, genome-wide transcriptome atlas and cost-effective high and low-density genotyping assays. These genomic resources have enabled high-resolution trait mapping by using germplasm diversity panels and multi-parent genetic populations leading to precise gene discovery and diagnostic marker development. Furthermore, development and deployment of diagnostic markers have facilitated screening early generation populations as well as marker-assisted backcrossing breeding leading to development and commercialization of some molecular breeding products in groundnut. Several new genomics applications/technologies such as genomic selection, speed breeding, mid-density genotyping assay and genome editing are in pipeline. The integration of these new technologies hold great promise for developing climate-smart, high yielding and more nutritious groundnut varieties in the post-genome era.

Identification of quantitative trait loci for yield and yield related traits in groundnut (Arachis hypogaea L.) under different water regimes in Niger and Senegal - Issa Faye; Manish K. Pandey; Falalou Hamidou; Abhishek Rathore; Ousmane Ndoye; Vincent Vadez; Rajeev K. Varshney (Euphytica, 2015)
Yield under drought stress is a highly complex trait with large influence to even a minor fluctuation in the environmental conditions. Genomics-assisted breeding holds great promise for improving such complex traits more efficiently in less time, but requires markers associated with the trait of interest. In this context, a recombinant inbred line mapping population (TAG 24 × ICGV 86031) was used to identify markers associated with quantitative trait loci (QTLs) for yield and yield related traits at two important locations of West Africa under well watered and water stress conditions. Among the traits analyzed under WS condition, the harvest index (HI) and the haulm yield (HYLD) were positively correlated with the pod yield (PYLD) and showed intermediate broad sense heritability. QTL analysis using phenotyping and genotyping data resulted in identification of 52 QTLs. These QTLs had low phenotypic variance (<12 %) for all the nine traits namely plant height, primary branching, SPAD chlorophyll meter reading, percentage of sound mature kernels, 100 kernel weight, shelling percentage, HI, HYLD and PYLD. Interestingly, few QTLs identified in this study were also overlapped with previously reported QTLs detected for drought tolerance related traits identified earlier in Indian environmental conditions using the same mapping population. Accumulating these many small-effect QTLs into a single genetic background is nearly impossible through marker-assisted backcrossing and even marker-assisted recurrent selection. Under such circumstances, the deployment of genomic selection is the most appropriate approach for improving such complex traits with more precision and in less time.